Mathematical approaches to seed germination - Hampstead, Anthony (2014)
Plant seeds progress through specific stages during germination, from quiescence in the dry state through water uptake, testa rupture and finally endosperm rupture. The stages of seed germination are fairly well classified but the underlying biochemical and mechanical processes are unknown. The ability to control a seeds progression through the stages of germination has implications on farming efficiency and so the following thesis explores Arabidopsis thaliana and Lepidium sativum seeds during the germination process.